1972
DOI: 10.1128/aem.24.6.958-966.1972
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Survey of the Blue Crab Industry

Abstract: During sanitation inspections of 46 crabmeat processing plants on the Atlantic and Gulf Coasts, 487 samples of whole crabs immediately after cooking, cooked crabs after cooling, backed or washed (or both) crab bodies and whole crab claws, as well as 1,506 retail units of finished product were collected and analyzed bacteriologically. The 1,506 retail units (1-lb [373.24-g ] cans) included 518 cans of regular (special) meat, 487 cans of claw meat, and 501 cans of lump meat. Statistical analyses showed that crab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Wentz et al (1984) showed that the bacteria of most importance in post-processed blue crab meat were Escherichia coli and Staphylococcus aureus. This was in agreement with an observation reported by Phillips and Peeler (1972). Recently, Betts (1992) indicated that the decimal reduction times for E. coli and S. aureus in beef were, respectively, 0.47 min at 62.8C and 1.36 min at 62C.…”
Section: Introductionsupporting
confidence: 92%
“…Wentz et al (1984) showed that the bacteria of most importance in post-processed blue crab meat were Escherichia coli and Staphylococcus aureus. This was in agreement with an observation reported by Phillips and Peeler (1972). Recently, Betts (1992) indicated that the decimal reduction times for E. coli and S. aureus in beef were, respectively, 0.47 min at 62.8C and 1.36 min at 62C.…”
Section: Introductionsupporting
confidence: 92%
“…1, 2, 4, and 5), microbial populations of the composite by-product over 4 days refrigerated storage ranged from lo5 to 10'. Surveys have shown that 90-93% of the processing plants operating under good sanitary conditions produced crab meat with mesophilic counts of less than 105/g (Phillips and Peeler, 1972;Wentz et al, 1985). The in-plant cooking process, i.e., 121°C for lo-23 min, was sufficient to reduce microbial numbers to relatively low levels.…”
Section: Short-term Refrigeration Study Of Minced Meatmentioning
confidence: 99%
“…Crabmeat is a highly perishable product and its microbial quality is further jeopardized by intensive handling such as backing, picking, and packing operations after cooking (Wentz et al 1985;Ward et al 1983). Handling causes severe post-cook contamination and shortens the shelf-life of the product (Slocum 1955;Phillips and Peeler 1972). Wentz et al (1985) found that the geometric mean aerobic plate count at 35C increased from 1,200 CFU/g (Colony Forming Units) before picking to 20,000 CFU/g in the finished product (body meat).…”
Section: Introductionmentioning
confidence: 99%